An integrative review of nursing students' clinical placement experiences throughout their nursing degrees. Issue 1 (February 2023) - Diane, Russ; Whiteing, Nicola; Aggar, Christina
ABSTRACT: Background: Clinical placement experience is closely linked to nursing students' decisions to withdraw from their nursing degrees. While most nursing students withdraw before the end of the first year, a proportion leave in the latter years. There is a need to understand students' experiences of clinical placement across the entirety of their program. Aim: To describe and explore nursing students' longitudinal clinical placement experience during the nursing degree. This information will inform strategies that can be scaffolded across the degree to support quality clinical placements. Methods: An integrative review utilising Whittemore and Knafl's framework. Studies published from 2010 to 2020 were identified using eight databases. Results: A total of 368 papers were located, seven met the inclusion criteria. Two themes emerged from analysis: support and the emerging practitioner. The central focus of the students' experience over time was present. Discussion: Clinical placement support during the nursing degree was paramount to the student experience, with the type and level of support changing over time. Development of supportive relationships is critical to nursing students' sense of belonging and connectedness. The importance of familiarity and continuity of place may positively influence student attrition and transition into the workforce. Conclusion: Provision of timely, appropriate support and an inclusive work environment is key to successful clinical placement experiences over time. This may be enhanced using a Collaborative Clinical Placement Program model. Further research is needed to explore students' longitudinal experience of clinical placements across the nursing degree.